The Local Government Transformation, The Big Five Personality And Anxiety - Amanda Pasca Rini,, Sri Rahayuningsih, Andik Matulessy,; Rumambo Pandin, Moses Glorino , (Opción, 2019)
The focus of research is to examine the correlation between the personality dimension and capability of adversity and anxiety of the staffs in organizational changes. The research used purposive sampling method before applied multiple regression analysis. As a result of data analysis showed evidence that the consequences of the uncertainty organizational change affected hope and comfort of the staffs, which was brought about by anxiety. In conclusion, staff anxiety facing organizational change is not only influenced by personality dimensions but also organizational culture and intelligence facing challenges or difficulties to be one of the predictors to watch out for.